Analysis Extension Program and Development of Artificial Insemination Forage Production on The Improvement of Beef Cattle in District Bondowoso - Niken Dyah Kusuma Dewi; Rizal Rizal; Hariadi Subagja (Universitas Tadulako, 2015)
To improve farm products particulary cattle production, The goverment ofBondowoso District did through some policy : (1) extension program, (2) artificial insemination and (3) forage development.Although the program has been launched, there are still many problems occured. It is indicated by decreasing population of cattle, the declined result of artificial insemination and decreasing of meat production. The purpose of this research to find out the effect of extension program, artificial insemination and the development of forage on the increasing of beef cattle in Kabupaten Bondowoso. This research used explanatory research with Structural Equation Modeling (SEM) analysis. The result showed that the extension program didn’t effect improvement of beef cattle production, but the production can be improved by artificial insemination and forage development.